علاقة أشكال الصبغين ألجنسي (Sex Chromatin) ببعض صفات الدم الأيضية في الأبل المحلي: هاشم مهدي الربيعي طالب احمد حامد الربيعي - الربيعي, هاشم مهدي (Journal of Kerbala for Agricultural Sciences, 2016)
أُجريت الدراسة في مُختبرات قسم تقنيات الأنتاج الحيواني في الكُلية التقنية / المسيب للمُدة من أب لغاية كانون الثاني 2015 , لدراسة أشكال الصبغين ألجنسي في خلايا كريات الدم البيض متعددة النوى (العِدلاَت) وعلاقتها ببعض الصفات الايضية في دم الأبل المحلي , وشملت الدراسة 20 أنثى من الأبل البالغة وتراوحت أعمارها من 6-12 سنة . سُحبت عينات الدم من وريد الحليب البطني وحُضرت المسحات الدموية وفُحصت لتحديد تواجد الصبغين ألجنسي وأشكالهُ وأبعادهُ . بينت النتائج أن النسبة المئوية لأشكال الصبغين ألجنسي عصا الطبال وبروز بدون ساق والهراوي ودمعة العين بلغت 60.85 و 24.25 و 8.32 و 6.57 % بالتتابُع. بلغ المتوسط العام للمحور الأفقي والعمودي ومساحة الصبغين ألجنسي 1.169 مايكرون و1.061 مايكرون و 0.973 مايكرون مربع بالتتابُع , ووصل المتوسط العام للمحور الأفقي والعمودي ومساحة النواة الى12.478 مايكرون و11.041 مايكرون و108.14 مايكرون مربع بالتتابُع , وبلغ عدد الفصوص بالنواة 3.826 فصاً , وبينت النتائج أيضا بوجود تأثيراً معنوياً (P<0.05) لشكل الصبغين ألجنسي على تركيز الكلوكوز والبروتين الكُلي بينما كان التأثير غير معنوي لشكل الصبغين على تركيز الكوليستيرول الكُلي والدهون الثُلاثية . نستنتج من هذه الدراسة امكانية التنبؤ ببعض الصفات الأيضية من خلال أبعاد الصبغين ألجنسي على كريات الدم البيض (العِدلات) وأستعمالها كوسيلة من وسائل الأنتخاب والتحسين الوراثي . الكلمات المفتاحية : الصبغين ألجنسي , المواد الأيضية , الأبل المحلي . البحث مستل من رسالة ماجستير للباحث الثاني Relationship of sex chromatin figures with some blood metabolites traits in local she-camels (Camelus dromedaries) Dr. H. M. Al-Rubaeae Talib A. H. Al-Rubaeae Abstract The study was conducted at laboratories of department of animal technical production, Technical college-Al-musaib from August to December 2015, to investigate figures of sex chromatin (SC) in polymorphonclear leucocytes (Neutrophiles) and relaltion to some blood metabolites in local she-camels (Camelus dromedaries) . The study included 20 adult she-camel (6-12 years old) . Blood samples were collected from abdominal milk vein , prepared of blood smear and examined to determine presence of (SC) and its figures and dimensions . The results showed that percentage of Drum stick (D) , Sessile Nodule (SN) , Small club (SM) and Tear drop (T) figures were 60.85, 24.25, 8.32 and 6.57 % respectively . The overall means of horizontal and vertical axes and sex chromatin area (SCA) were 1.169 microns (µm) , 1.061 µm and 0.973 µm² respectively , and the overall means of horizontal and vertical axes and nuclear area (NA) were 12.478µm, 11.041 µm and 108.14 µm² respectively . The overall means of the number of lobes reached 3.826 lobes . The results also showed that significant effect (P< 0.05) of (SC) figures on glucose and total protein concentrations , While the effect was non-significant on total cholesterol and triglycerides concentrations . In conclusions , possibility to predicting of some metabolites traits through dimensions of sex chromatin in polymorphonuclear leucocytes ( Neutrophiles) to use as a means of selection and genetic improvement . Key word : Sex chromatin , Metabolites , Local she camels .